Economic relations between Germany and Japan: An analysis of recent data - Werner Pascha (Universität Duisburg-Essen, Forschungsinstitut für Wirtschaftliche Entwicklungen im Pazifikraum (FIP), 2002)
The author takes a close look at bilateral German-Japanese trade and direct investment data, employing various techniques (intensity indicators, RCA, intra-industry trade). It turns out that German-Japanese trade and FDI links are indeed rather limited, as has frequently been stated. A number of somewhat surprising pieces of evidence do emerge, though. For competitive industries and with respect to emerging opportunities, the bilateral figures do show a healthy performance.
Keywords: 330; foreign trade; foreign direct investment; Japan; Germany